The effect of internal factors on tax audit effectiveness in the Royal Malaysian Customs Department (RMCD) - Norasmah, Md Yusof (2023)
Industrial Revolution 4.0 saw changes in the world economy forcing most of the tax authorities to change tax administration towards digitalization. Manual tax audits and investigations have been replaced using technology that is able to help tax administrators select high-risk audit cases and prepare taxpayer profiles. Developing countries such as Malaysia face technological constraints in the auditing process, plus the country's financial position is in a deficit position; therefore, the available option is to increase the effectiveness of tax audits. In connection with that, a study was conducted on officers in the Compliance Division, Royal Malaysian Customs Department (RMCD), to assess the effect of internal factors, namely audit case selection, auditor competence, and management support, on the effectiveness of tax audits. This study is quantitative in nature and uses an online questionnaire as a research instrument. Only senior customs officers are on duty as tax auditors in eight selected states in Peninsular Malaysia selected as respondents. Based on the analysis of data from 139 respondents, the results of the study found that only the selection of audit cases and management support had a significant and positive effect on the effectiveness of tax audits. However, the auditor competency does not have any effect on the effectiveness of tax audits in RMCD. The results of this study can empirically prove the influence of internal factors on the effectiveness of tax audits. In addition, the results of the study are relevant to RMCD, specifically as a guide for improving audit performance and tax revenue.